1990
DOI: 10.1016/0278-6915(90)90008-b
|View full text |Cite
|
Sign up to set email alerts
|

The carcinogenic potential of ethyl carbamate (urethane): Risk assessment at human dietary exposure levels

Abstract: Summary-Ethyl carbamate is found in fermented foods: bread contains 3-15 ng/g, stone-fruit brandies 200-20,000 ngfg, and about one-third of table-wine samples analysed contained more than 10 ng/g. In animals, ethyl carbamate is degraded to C0 2 , H 2 0 and NH 3 , with intermediate formation ofethanol. This degradation has been shown tobe inhibited (postponed) in the mouse by ethanol concentrations in the blood of about 0.15% and higher. A quantitatively minor pathway involves a two-step oxidation of the ethyl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0
4

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(54 citation statements)
references
References 23 publications
0
50
0
4
Order By: Relevance
“…However, some wines have been reported to have arginine levels as high as 2 to 5 g liter Ϫ1 after alcoholic fermentation (4,10,27). In a recent long-term study of the formation of EC in (24). Considering these values, addition of citrulline to the EC precursor pool by arginine-degrading MLB may lead to exceeding existing or future voluntary or legal EC limits.…”
Section: Discussionmentioning
confidence: 99%
“…However, some wines have been reported to have arginine levels as high as 2 to 5 g liter Ϫ1 after alcoholic fermentation (4,10,27). In a recent long-term study of the formation of EC in (24). Considering these values, addition of citrulline to the EC precursor pool by arginine-degrading MLB may lead to exceeding existing or future voluntary or legal EC limits.…”
Section: Discussionmentioning
confidence: 99%
“…It can be found in fermented foods and beverages like spirits, wine, beer, bread, soy sauce and yoghurt (Conacher and Page, 1986;Dennis et al, 1989;Battaglia et al, 1990;Schlatter and Lutz, 1990;Zimmerli and Schlatter, 1991;Sen et al, 1992;Sen et al, 1993;Benson and Beland, 1997;Kim et al, 2000). The structure and two routes of the formation of ethyl carbamate are illustrated in Figure 1.…”
Section: Terms Of Reference As Provided By Requestormentioning
confidence: 99%
“…Kim et al 3 reported that Koreans were exposed to up to 2.8 µg EC day −1 , which is not a negligible amount considering the 'virtually safe dose' suggested by Schlatter and Lutz. 4 Although the contribution of soy sauce to daily EC intake was rated second highest among Korean food items, the range of EC levels in soy sauce (ND-73.3 µg kg −1 , where ND denotes 'not detected') was found to be about four times broader than that in kimchi (ND-16.2 µg kg −1 ). 3 Kimchi, a fermented vegetable product made with varying amounts of different ingredients, including Korean cabbage, red pepper, garlic and other vegetables, is an important source of EC owing to its high daily consumption by Koreans.…”
Section: Introductionmentioning
confidence: 97%